Analisis Kinerja Keuangan Sebelum dan Sesudah Akuisisi pada Perusahaan Industri Musik Korea Selatan: HYBE Corporation - Ni Putu Melia Astuti; I Gde Ary Wirajaya (Jurnal Bisnis dan Kewirausahaan, 2023)
Business expansion through acquisition has the purpose to increase company performance which is one of corporate action and also the way a company can compete with their competitors healthily. This research aims to get a proof empirical about whether there’s a difference or not on HYBE Corporation’s company performance after acquiring Ithaca Holdings. Object that used on this research is HYBE Corporation’s quarterly consolidation financial reporting. Company performance in this research evaluated by financial ratio. Analysis methods that used in this research are paired sample t-test and wilcoxon signed rank test. Result of this research shows that there’s no difference with HYBE Corporation’s company performance after acquired Ithaca Holdings.